(untitled) (Bangladesh Agronomy Journal, 2021)
The experiment was conducted in pot at the net house of the department of Agronomy, Sher-e-Bangla Agricultural University, Dhaka during the period from November, 2018 to March, 2019to find out the optimum dose(s) cowdung to mitigate the water deficit effect on wheat. The experiment comprised of two factors viz. factor A: Five levels of cowdung, i) C0= Control (No cowdung), C1= 25% less cowdung of recommended dose, C2 = Recommended dose of cowdung, C3 = 25% higher cowdung of recommended dose and C4 = 50% higher cowdung of recommended dose, and factor B: four levels of water deficit at, i) D0 = Control (No water deficit), D1= Crown root initiation stage (20-19 DAS), D2 = Booting stage (45-54 DAS) and D3= An thesis stage (55-64 DAS). The experiment was laid out in a Factorial R and omized Complete Block Design with three replications. The test crop variety was BARI Gom28. The result reveled that cowdung level had positive impact on yield of wheat under water deficit condition, and 50% higher cowdung of recommended dose (C4) gave the highest grain yield (5.12g plant-1). The particular treatment also produced the highest number of effective tillers plant-1 (5.25), spike length (10.39 cm), spikelet spike-1 (15.72), grains spike-1 (32.56), grains spikelet-1 (2.07) and 1000-grain weight (47.32 g) of wheat. The treatment C3 (25% higher cowdung of recommended dose) also gave statistically similar yield with C4 treatment. In respect of water deficit imposition treatments, grain yield was found the highest in control treatment which was statistically similar with water deficit imposition at booting stage treatment (D2). These two treatments also showed the higher and similar number of effective tillers plant-1 (4.86 and 4.58), spike length (10.53cm and 10.11cm), spikelets spike-1(15.50 and 15.19), grains spike-1 (34.10 and 30.17), grains spikelet-1 (2.20 and 1.98) and 1000-grain weight (45.42g and 45.36g, respectively). Regarding the interaction of levels of cowdung and water deficit imposition at different stages of plant growth, C4D0 and C3D0 were highest yielder which was attributed to higher 1000-seed weight, number of effective tillers plant-1, spikelets spike-1 and grains spike-1. Contrary, 25% higher cowdung than recommended dose (as it saved 25% cowdung) seems promising to overcome yield loss due to water deficit imposition at booting stage of wheat (D2). However, application of cowdung (12.5 t ha-1) was found effective to combat water deficit at booting stage (D2) of wheat compared to other growth stages. Bangladesh Agron. J. 2021, 24(1): 93-100